2018
DOI: 10.1111/joa.12917
|View full text |Cite
|
Sign up to set email alerts
|

Sequential testicular atrophy involves changes in cellular proliferation and apoptosis associated with variations in aromatase P450 expression levels in Irs‐2‐deficient mice

Abstract: Insulin receptor substrate 2 (Irs‐2) is an intracellular protein susceptible to phosphorylation after activation of the insulin receptor. Its suppression affects testis development and its absence induces peripheral resistance to insulin. The aim of this study was to identify changes induced by the deletion of Irs‐2 in the testicular structure and by the altered expression of cytochrome P450 aromatase, a protein necessary for the development and maturation of germ cells. Adult knockout (KO) mice (Irs‐2−/−, 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…We also detected round spermatids with malformed acrosomal structures in Ssh2 KO testes, which suggests that the acrosome formation was also affected. Furthermore, clustered round spermatids and apoptotic-like germ cells exhibiting small hyperchromatic nuclei and polynuclear structures, which are known indicators of apoptosis (Catalano-Iniesta et al, 2019), were observed in Ssh2 KO tubules (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…We also detected round spermatids with malformed acrosomal structures in Ssh2 KO testes, which suggests that the acrosome formation was also affected. Furthermore, clustered round spermatids and apoptotic-like germ cells exhibiting small hyperchromatic nuclei and polynuclear structures, which are known indicators of apoptosis (Catalano-Iniesta et al, 2019), were observed in Ssh2 KO tubules (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a reduction in the miRNAs targeting foxo3a suggests a positive regulation of this transcription factor, consequently activating the FoxO signaling pathway. In addition, several other genes downstream from the coding region for foxo3a transcription factor have also shown to be targeted by the down-regulated miRNAs, further implying their importance in this pathway (by themselves or in association with PI3K/Akt signaling pathway) in spermatic cells of gh + zebrafish ( Griffeth et al, 2013 ; Capra et al, 2017 ; Zhang et al, 2017b ; Catalano-Iniesta et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%